Mengembangkan Kemampuan Motorik Kasar Melalui Bermain Asenan Pada Anak Usia 5-6 Tahun Di Taman Kanak-Kanak (Tk) Negeri 01 Anggana Kutai Kartanegara - Retno Lusianik; Heppy Liana; Yeni Aslina (Manajemen Pendidikan Program Doktor, 2025)
The purpose of this study is as follows: 1) to determine the development of gross motor skills through playing asenan in group B children aged 5-6 years in State Kindergarten (TK) 01 Anggana. 2) to determine how asenan games can develop gross motor skills in group B children aged 5-6 years in State Kindergarten (TK) 01 Anggana. This research method uses qualitative research methods. Data collection techniques include observation, interviews and documentation. Data analysis includes data reduction, data presentation and drawing conclusions. The conclusion of the results of this study is to develop gross motor skills through playing asenan in group B children aged 5-6 years in State Kindergarten (TK) 01 Anggana, their gross motor skills have not developed optimally. So it is necessary to have stimulation in improving gross motor development by using the asenan playing method. In order to achieve learning objectives that are in accordance with the gross motor development indicators in children aged 5-6 years, the researcher chose that the Asenan playing method can improve the gross motor development of children aged 5-6 years at the State Kindergarten (TK) 01 Anggana.